Molecular Detection of Dapsone and Rifampicin Resistance on Mycobacterium leprae from Leprosy Patients in East Java - DINAR ADRIATY; RATNA WAHYUNI; CITA ROSITA S. PRAKOESWA; NI PUTU SUSARI; INDROPO AGUSNI; SHINZO IZUMI (Indonesian Society for microbiology, 2009)
The drug resistant problem of Mycobacterium leprae has been developing since the last decade and this has become a leprosy elimination problem in several countries, including Indonesia. Using biological on molecular methods, it is now possible to test for drug resistant cases in relatively simple and less time consuming ways. The purpose of the study is to analyze theprevalence of drug resistance M. leprae to dapsone and rifampicin in East Java based on the etection of mutations in the folP and rpoB genes. All samples were obtained from multibacillary leprosy patients in East Java, who have admitted to the Dr Sutomo Hospital Surabaya in 2003-2005. Isolates were analyzed by PCR, and the presence of nucleotide sequence of the folP and rpoB genes from M. leprae were confirmed by direct sequencing. Of 94 specimens which were collected, all were analyzed for their folP and rpoB genome. From 94 isolates, 70 showed a positive result by the folP1-folPR test and 77 out of 94 isolates showed positive by the rpoBF-rpoBR test. From 70 isolates for folP gene examination, there were 3 isolates which had mutation in the amino acid at codon 53; 2 cases Threonin (ACC) became Alanin (GCC) and 1 case Threonin (ACC) became Arginin (AGA). These mutations are responsible to dapsone resistance. For the rpoB gene, no mutation was found. The result suggested that 3 isolates (4.3%), 1 from a new case and 2 from relapse cases in this experiment, were resistant to dapsone and all isolates (100%) were susceptible to rifampicin.